MEMS Dielectrophoresis Device for Osteoblast Cell Stimulation - Zou, H; Syms, R; Mellon, S; Tanner, K (2009)
A fixed microelectrode device for cell stimulation has been designed and fabricated using micro-electromechanical systems (MEMS) technology. Dielectrophoretic forces obtained from non-uniform electric fields were used for manipulating and positioning osteoblasts. The experiments show that the osteoblasts experience positive dielectrophoresis (p-DEP) when suspended in iso-osmotic culture medium and exposed to AC fields at 5 MHz frequency. This work will help to investigate the mechanisms underlying Wolffs law of bone growth dynamics at the cellular level. The methods used can also be developed to control osteoblast metabolism and ultimately enhance bone repair processes. © 2009 Trans Tech Publications, Switzerland.